Assessment Of Hazard Problems In Workplace Related To Emergency Response Plan For Employees In Primary Health Care Centers At Babylon City. - Hussein Kadhim Abbood (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
The study titled " Assessment of Hazard Problems in Workplace Related to Emergency Response Plan for employees in Primary Health Care centers at Babylon City." explores the significance of workplace safety through the implementation of occupational safety policies and regular inspections. The primary research question addresses whether the emergency response plan (ERP) in these healthcare centers is genuinely effective or merely a formality, highlighting that employees lack sufficient information about the ERP. The study aims to evaluate workplace risk problems, including fire alarm systems, emergency exits, regular employee check-ups, and medical waste disposal. Conducted between January 2 and March 30, 2018, in Babylon's primary healthcare centers, this descriptive quantitative study utilized a specially developed assessment tool and data collection through a quarterly supervisory form. Key findings indicate that 85% of the surrounding environment is suitable, 46% of sanitation systems are adequate, 96% of fire extinguishers are available, and 52% of emergency exits are accessible. Recommendations emphasize enhancing employee training on the ERP, conducting regular safety system inspections, and raising awareness of occupational safety's importance among staff.